The correlation between viral clearance and biochemical outcomes of 94 COVID-19 infected discharged patients - Yuan, Jing; Zou, Rougrong; Zeng, Lijiao; Kou, Shanglong; Lan, Jianfeng; Li, Xiaohe; Liang, Yanhua; Ding, Xiaoyan; Tan, Guoyu; Tang, Shenghong; Liu, Lei; Liu, Yingxia; et al. (Inflammation research, 2020)
Objective This study aims to evaluate the correlation between viral clearance and blood biochemical index of 94 discharged patients with COVID-19 infection in Shenzhen Third People’s Hospital, enrolled from Jan 5 to Feb 13, 2020. Methods The clinical and laboratory findings were extracted from the electronic medical records of the patients. The data were analysed and reviewed by a trained team of physicians. Information on clinical signs and symptoms, medical treatment, virus clearance, and laboratory parameters including interleukin 6 (IL-6) and C-reactive protein were collected. Results COVID-19 mRNA clearance ratio was identified significantly correlated with the decline of serum creatine kinase (CK) and lactate dehydrogenase (LDH) levels. Furthermore, COVID-19 mRNA clearance time was positively correlated with the length of hospital stay in patients treated with either IFN-α + lopinavir/ritonavir or IFN-α + lopinavir/ritonavir + ribavirin. Conclusions Therapeutic regimens of IFN-α + lopinavir/ritonavir and IFN-α + lopinavir/ritonavir + ribavirin might be beneficial for treatment of COVID-19. Serum LDH or CK decline may predict a favorable response to treatment of COVID-19 infection.